O MDB ao MDB: um mapeamento da atuação parlamentar - Carvalho, Guilherme Augusto Batista (2019)
This work is devoted to investigating the parliamentary role of the MDB in the Chamber of Deputies over a period of twenty-three years, 1995-2017. The paper tries to understand how the MDB (P)MDB, with several internal divisions and structural difficulties for block decision making, behaves in a relatively stable way, and maintains an indispensable party in the composition of the ministries? To investigate, we analyze the institutional mechanisms used by the party in the Chamber of Deputies, such as the control of the agenda of various thematic commissions and mechanisms of regimentation of the support bases, given by the Federal Executive, such as appointments to ministerial positions and release of budget amendments individuals. to remain a party resilient to crises of governability, Based on the research findings, it is believed that the (P)MDB uses institutional instruments to elect large groups, to occupy the highest number of leadership positions in the Chamber, being able to occupy large positions in the Executive, thus having more access to the budget, thus increasing the exposure of its coreligionists at the local level, and, in short, increasing the chances of re-electing bigger groups. The findings of the research allow us to affirm that the (P)MDB uses institutional instruments to elect large groups, to occupy the highest number of leadership positions in the Chamber, being able to occupy large positions in the Executive, therefore having more access to the budget, thus increasing the exposure of their coreligionists at the local level, and, in short, increasing the chances of re-electing bigger groups.